Reason and the heart : a prolegomenon to a critique of passional reason - Wainwright, William J. (Cornell studies in the philosophy of religion., 1995)
Between the opposing claims of reason and religious subjectivity may be a middle ground, William J. Wainwright argues. His book is a philosophical reflection on the role of emotion in guiding reason. There is evidence, he contends, that reason functions properly only when informed by a rightly disposed heart.